2017
DOI: 10.1002/jmcd.12076
|View full text |Cite
|
Sign up to set email alerts
|

Racial Discrimination and Health Outcomes Among Racial/Ethnic Minorities: A Meta‐Analytic Review

Abstract: In this meta-analysis, the authors reviewed 105 studies on the relationships between racial discrimination and health outcomes among racial/ethnic minority Americans. The authors tested for moderator effects of measurement strategies, cultural factors, substance use, gender, and racial group differences. Findings indicate a statistically significant effect size between racial discrimination and health, with the largest effect for mental health and strongest for studies with multi-item measures.En este metaanál… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
145
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 215 publications
(167 citation statements)
references
References 127 publications
8
145
0
1
Order By: Relevance
“…Across diverse ethnic populations, positive associations were found between ethnic discrimination and emotional distress, as well as inverse associations with positive markers of well‐being, such as self‐esteem and self‐efficacy . Several recent reviews continue to document an inverse association between discrimination and good mental health . For example, a 2014 review reported the results of two meta‐analyses focused on the association between discrimination and well‐being .…”
Section: Resultsmentioning
confidence: 99%
“…Across diverse ethnic populations, positive associations were found between ethnic discrimination and emotional distress, as well as inverse associations with positive markers of well‐being, such as self‐esteem and self‐efficacy . Several recent reviews continue to document an inverse association between discrimination and good mental health . For example, a 2014 review reported the results of two meta‐analyses focused on the association between discrimination and well‐being .…”
Section: Resultsmentioning
confidence: 99%
“…Database selection is consistent with previous reviews of racial discrimination and health outcomes [29][30][31]. Searches were conducted during August to September 2017 with the PubMed and PsychINFO online databases using the following search terms: (racial discrimination, racism, OR, prejudice) AND (Black or African-American) AND alcohol.…”
Section: Literature Searchmentioning
confidence: 99%
“…Discrimination is the act of denying individuals equal treatment on the basis of group membership (Allport, 1954); racial discrimination refers to unfair treatment of persons or groups due to race or ethnicity (Pager & Shepherd, 2008). This form of discrimination has attracted close attention across domains including mental and physical health (Carter, Lau, Johnson, & Kirkinis, 2017), personality and social psychology (Sellers & Shelton, 2003), workplace behaviour (Triana, Jayasinghe, & Pieper, 2015), politics (Peffley, Hurwitz, & Mondak, 2017), criminology (Unnever, Cullen, & Barnes, 2017), and law (Wintemute, 2017). Scholars have examined the antecedents and consequences of racial discrimination from multiple perspectives.…”
Section: Introductionmentioning
confidence: 99%